The Cultural Meaning of Colonial Power in Residentwoning Palembang - Dedi Irwanto (Criksetra: Jurnal Pendidikan Sejarah, 2024)
Abstract: In the early colonial era, palace buildings served as residentwoning. This article examines how form, architecture, materials, and technology were used to create Palembang residentwoning. The symbolic meaning of the residentwoning is where the analysis of the changes is situated. This research uses historical methods in critically examining and analyzing recorded remains of the past. The approach in this study is description-analysis based on symbolic meaning. This study's analysis indicates that the Palembang residentwoning can take the place of the Palembang sultanate palace as the hub for political administration, both military and civil. Since the residentwoning was established during the early days of the Dutch administration in Palembang, it has actually contributed to the local economy by upholding compliance through verbal and visual cues highlighting the residence's grandeur as the Palembang Residency's ruler. The uluan people of Palembang planted a variety of commercial commodities, including coffee, tea, cotton, rubber, and palm oil, as ordered by the residentwoning. This eventually resulted in the advancement of trade in the colonial city of Palembang. Abstrak: Artikel ini menganalisis perubahan alih fungsi bangunan kraton ke rumah residen masa awal kolonial, termasuk fungsi bentuk, arsitektur, bahan, dan teknologi. Analisis perubahan ditempatkan dalam pemaknaan simbolik kehadiran rumah residen. Penelitian menggunakan metode historis dalam menguji rekaman tinggalan masa lalu secara kritis. Pendekatan kajian ini adalah deskripsi-analisis berdasar symbolic meaning. Analisis kajian ini menunjukkan kehadiran rumah residen mampu menggantikan kraton Kesultanan Palembang, baik sebagai pusat administrasi politik sipil maupun militer. Bahkan kehadiran rumah residen di awal pemerintah Belanda di Palembang, secara kultural menjadi penggerak perekonomian daerah-daerah uluan Palembang dengan cara menjaga kepatuhan lewat visual dan non-verbal dari kebesaran rumah residen sebagai penguasa di Keresidenan Palembang. Melalui perintah-perintah dari rumah residen, masyarakat uluan di Palembang akan patuh menanam berbagai komoditas komersil seperti kopi, teh, kapas, karet, dan kelapa sawit yang akhirnya menjadi kemajuan perdagangan di Kota Palembang masa kolonial.